From the Interregnum (1382) to the Rule of Jadwiga and Władysław Jagiełło. From the History of the Social Advancement of the Łęczyca Nobility in the 14th and 15th Centuries - Ćwikła, Łukasz (Social consequences of war, 2024)
This article traces the careers of selected noble families whose representatives became active during the interregnum after the death of Louis of Hungary (1382). They represented the Doliwa, Jastrzębiec, Junosza and Sulima families. The situation in the Kingdom of Poland was tense, because Polish society was divided into two camps that pushed for different concepts of taking the Polish throne. The Angevin and Piast options clashed. Due to their location, the lands of Łęczyca and Sieradz were also at the center of these events. In the final phase of the conflict, Siemowit IV decided to take over Łęczyca, and the capital Łęczyca was attacked by a unit commanded by Bartosz from Odolanów – the capital city was devastated and burned. The involvement of the local nobility in current political events brought them tangible benefits soon, because so far they had not played a leading political role. The fortunes of war and the complicated legal and political situation of the Łęczyca region at that time ultimately led to them taking up offices (many received their first offices during Jadwiga’s lifetime) and, as a consequence, brought social advancement, from which subsequent generations also benefited. The key to the promotion was, of course, the policy of Władysław Jagiełło, who gained new supporters by handing out offices. The article also attempts to identify Siemowit IV’s probable supporters among the Łęczyca nobility, pointing to the Junosza family from Orłów, who came from Masovia, where Siemowit III and Siemowit IV ruled.